Hyperglycemia and Physical Impairment in Frail Hypertensive Older Adults - Pansini, Antonella; Lombardi, Angela; Morgante, Maria; Frullone, Salvatore; Marro, Anna; Rizzo, Mario; Martinelli, Giuseppe; Boccalone, Eugenio; De Luca, Antonio; Santulli, Gaetano; Mone, Pasquale (Frontiers in Endocrinology, 2022)
Background Frailty is a multidimensional condition typical of elders. Frail older adults have a high risk of functional decline, hospitalization, and mortality. Hypertension is one of the most common comorbidities in elders. Hyperglycemia (HG) is frequently observed in frail older adults, and represents an independent predictor of worst outcomes, with or without diabetes mellitus (DM). We aimed at investigating the impact of HG on physical impairment in frailty. Methods We studied consecutive older adults with frailty and hypertension at the ASL (local health unit of the Italian Ministry of Health) of Avellino, Italy, from March 2021 to September 2021. Exclusion criteria were: age <65 years, no frailty, no hypertension, left ventricular ejection fraction <25%, previous myocardial infarction, previous primary percutaneous coronary intervention and/or coronary artery bypass grafting. Blood glucose, Hb1Ac, and creatinine were measured in all patients. Physical frailty was assessed applying the Fried Criteria; we performed a 5-meter gait speed (5mGS) test in all patients. Results 149 frail hypertensive older adults were enrolled in the study, of which 82 had normoglycemia (NG), and 67 had HG. We observed a significantly slower 5mGS in the HG group compared to the NG group (0.52 ± 0.1 vs. 0.69 ± 0.06; p<0.001). Moreover, we found a strong and significant correlation between 5mGS and glycemia (r: 0.833; p<0.001). A multivariable linear regression analysis using 5mGS as a dependent variable revealed a significant independent association with glycemia (p<0.001) after adjusting for likely confounders. Conclusions HG drives physical impairment in frail hypertensive older adults independently of DM.